FUTURE ORGANIZATIONAL CHANGE AND DEVELOPMENT STRATEGY: A SYSTEMIC LITERATURE REVIEW BASED ON BEHAVIORAL, VALUE, AND SUSTAINABILITY THEORIES - Nasra; Anton Dody Rushendra; Siti Rabiah; Ameliya Bangun; Tetra Hidayati (CV. RADJA PUBLIKA, 2025)
This article conducts a systematic literature review on prospective organizational change and development strategies, integrating behavioral theory, value-based approaches, and sustainability as foundational elements. The dynamics of global change and imperatives of sustainability necessitate that organizations undergo adaptive and transformative transformations, thereby reinforcing a collaborative work culture. The synthesis of findings indicates that the success of organizational change is significantly influenced by the synergy between individual behavioral transformation, value congruence, and the adoption of sustainable strategies underpinned by authentic leadership. This literature review also identifies research gaps, including the limited integration of individual behavioral theory with organizational change management practices, the scarcity of empirical studies on the relationship between values-based interventions and sustainability, and the need for cross-sector best practice research. This study offers new perspectives, maps key trends, and provides strategic recommendations for the development of resilient, inclusive, and competitive organizations in the future.